1928
DOI: 10.1002/prac.19281200121
|View full text |Cite
|
Sign up to set email alerts
|

Über organische Quecksilberbasen und ihre Salze

Abstract: I. Bisherige Darstellung der n‐Alkyl‐quecksilber‐basen und ihrer Salze. – Ursachen erneuter Bearbeitung dieser Körperklasse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1932
1932
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Slotta and Jacobi first reported "methyl mercuric hydroxide" in 1929. [1] However subsequent investigations gave wildly differing physical properties with melting points ranging from 95-137°C for apparently the same compound. Grdenic and Zado resolved this system when they concluded that "MeHgOH"…”
Section: Introductionmentioning
confidence: 99%
“…Slotta and Jacobi first reported "methyl mercuric hydroxide" in 1929. [1] However subsequent investigations gave wildly differing physical properties with melting points ranging from 95-137°C for apparently the same compound. Grdenic and Zado resolved this system when they concluded that "MeHgOH"…”
Section: Introductionmentioning
confidence: 99%
“…Anal. Calcd for C7H7HgC1: C, 29 N-Phenyl-2-butylsuccinimide. To a solution of 0.44 g (2.54 mmol) of NPM and 0.57 g (1.69 mmol) of 1-butylmercuric bromide in 5 mL of CH2C12 was added a solution of 0.128 g (3.38 mmol) of NaBH, in 0.5 mL of H20.…”
Section: Methodsmentioning
confidence: 99%
“…Ethylmercuric hydroxide was synthesized by a published method (17). All other reagents and solvents were analytical reagent grade'.…”
Section: Methodsmentioning
confidence: 99%